Application method of anti-carburizing coating

By using anti-carburizing coatings in carburizing furnaces, including substrate pretreatment and adding microcapsules to the coating, the corrosion problem of steel plates is solved, better insulation and anti-seepage effects are achieved, and cost and maintenance needs are reduced.

CN119186962AInactive Publication Date: 2024-12-27JIANGSU KINGKIND IND FURNACE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411113519.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In carburizing furnaces, the steel plate between the upper end of the muffle and the furnace cover ring plate causes carbon atom grain boundary corrosion due to temperature differences, short service life, poor insulation effect, and the existing anti-carburizing coatings are costly.

Method used

The methods of using anti-carburizing coatings include substrate pretreatment, coating stirring and coating, staged heating and insulation, microcapsules are added to the coating to achieve self-healing function, and the density and anti-seepage performance are improved through nano-silica. .

Benefits of technology

It extends the service life of the steel plate, improves the insulation and anti-seepage effects, shortens the process time, reduces the cost of use and maintenance, and the coating is not easy to age, fall off, or crack.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186962A_ABST
    Figure CN119186962A_ABST
Patent Text Reader

Abstract

The invention discloses a use method of an anti-carburizing coating, and relates to the technical field of coatings, and the use method comprises the following steps: S1, pretreating the surface of a base material; s2, stirring the coating; s3, coating of the coating; s4, drying the coating; s5, staged heating and heat preservation; according to the using method of the anti-carburizing coating, the current situation that a steel plate is corroded due to carburization is solved, the heat preservation effect of a furnace is better, the anti-carburizing effect is better, the process time is greatly shortened, the using cost and the maintenance cost are greatly reduced, and the service life of equipment is prolonged; and the anti-carburizing coating is not easy to age, does not fall off, does not crack and is relatively long in service life, so that the replacement and maintenance cost is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a method for using an anti-carburizing coating. Background Art

[0002] At present, it is known that the temperature between the furnace cover ring plate and the upper steel plate of the muffle inside the carburizing furnace is lower than the temperature in the furnace tank. Generally, the temperature in the furnace tank is about 900°C, but the temperature between the furnace cover ring plate and the upper steel plate of the muffle will drop to about 700°C due to factors such as the cooling water on the furnace cover, and 700°C is the temperature at which carbon black is most easily formed. In the long run, the steel plate between the upper end of the muffle and the furnace cover ring plate will slowly be corroded by the carbon atom grain boundary, resulting in short service life, poor thermal insulation effect, extended process time and other problems. In addition, a method for using an anti-carburizing coating is relatively high. For this reason, the present invention proposes a method for using an anti-carburizing coating to reduce the corrosion of the steel plate between the upper end of the muffle and the furnace cover ring plate. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a method for using an anti-carburization coating, which solves the problems raised in the background technology.

[0004] To achieve the above purpose, the present invention is implemented by the following technical scheme: a method for using an anti-carburizing coating, the steps of which are as follows: S1: Pretreatment of the substrate surface; clean the substrate surface thoroughly to remove oil and rust. First, wipe off the anti-rust oil with cotton yarn, then use 8112 cleaning agent to wash off the residual oil. After cleaning with the cleaning agent, put it into the furnace and keep it at 400℃ for 2-4 hours to remove the oil. S2: stirring the coating; the prepared microcapsules are evenly dispersed in the coating matrix, and the coating is fully stirred before application, using a shake bottle, a stainless steel rod or an electric stirrer for stirring. After stirring, the coating is poured into a stainless steel or plastic cup for use; S3: Coating; the coating is applied by brushing, spraying or dipping; the coating should be uniform, the thickness of the anti-carburizing coating is controlled at 0.1-0.2mm, and the coating density is 2.1-2.5g / cm³; S4: Drying of the coating; natural drying can be achieved by placing it in a ventilated place at room temperature for 24 hours, or baking it in a 60℃ oven for 2 hours; S5: Staged heating and heat preservation: After the coating is dried, the carburizing furnace is heated and heat preserved in stages.

[0005] Preferably, the anti-carburizing performance of the carburizing furnace after staged heating and insulation requires that the maximum carbon increase within 1 mm is less than 0.11%, the air gap should be controlled at ≤0.05 mm, and the refractoriness should reach ≥1500°C.

[0006] Preferably, in S1, for rust that is difficult to peel off, a mechanical removal method is used, such as sandblasting, shot blasting or chemical cleaning, and the chemical cleaning method is performed by soaking the substrate in a 10%-15% NaOH solution at 60-80° C. for 2-3 hours; Among them, sandblasting can increase the roughness of the metal surface, provide more mechanical anchoring points for the coating, and enhance the adhesion effect of the coating.

[0007] Preferably, in S1, the pores and honeycomb surface defects on the substrate surface need to be repaired, and the substrate surface needs to be cleaned with a high-pressure water gun, and the substrate surface needs to be pretreated, including pickling, acid solution immersion, and anodizing to form a layer of chemical substances on the substrate surface to improve the metal deposition effect; Among them, pretreatment methods such as pickling, acid solution immersion and anodizing can remove oil, rust and other impurities on the metal surface, thereby improving the adhesion between the coating and the metal substrate, thereby forming a uniform substrate surface with good adhesion, which helps the coating to form a uniform coating and improve the corrosion resistance, weather resistance and overall protective performance of the coating.

[0008] Preferably, the coating in S2 is composed of the following components and mass fractions: 10-15 anti-carburizing agent, 19-25 glass powder, 6-10 silicon dioxide powder, 5-10 borax, 3-6 aluminum oxide, 4-8 dolomite powder, 40-50 sodium silicate, 6-10 nano-silicon dioxide and the remainder water; wherein the anti-carburizing agent is copper oxide powder with a purity of ≥99.0% and a particle size range of 180-200 mesh, and the dolomite powder refers to dolomite powder containing 28%-30.4% calcium oxide by mass and 18%-21.9% magnesium oxide by mass.

[0009] Among them, the density and anti-seepage performance of the coating can be improved by using nano-silicon dioxide in the formula. Nano-materials can effectively improve the overall performance of the coating due to their small size effect and surface effect.

[0010] Preferably, the coating preparation method is as follows: Step 1: Grind the anti-carburizing agent, glass powder, nano-silicon dioxide, silicon dioxide, borax, alumina and dolomite powder in a ball mill. The speed of the ball mill is 400rpm-500rpm. The discharge temperature after grinding is lower than 30°C. The grinding time is 70-90min. The powder with a particle size D≤10μm is set aside. Step 2: Add the formulated amount of water glass to the powder in step 1, stir evenly, and when the viscosity reaches the range of 6000mPa•s-7000mPa•s, the finished anti-carburizing coating is obtained.

[0011] Preferably, the mass percentage of borax is ≥99.5%, and the particle size range is 70-80 mesh; the mass percentage of silicon dioxide is ≥99.0%, and the particle size range is 170-200 mesh; the mass percentage of aluminum oxide is ≥99.0%, and the particle size range is 200-230 mesh.

[0012] Preferably, in S3, the working temperature is 15-30° C. when dip coating is adopted, the thickness of one dip coating is controlled at 20-30 μm, the spraying distance is controlled at 30-35 cm when spray coating is adopted, and the moving speed of the spray gun is controlled at the range of 30-60 cm / s.

[0013] Preferably, the multi-stage stepped heating is respectively the first stage, the second stage, the third stage, the fourth stage and the fifth stage, wherein the substrate is heated to 35°C-45°C in the first stage and kept warm for 22h-26h, the substrate is heated to 75°C-85°C in the second stage and kept warm for 5h-7h; the substrate is heated to 95°C-105°C in the third stage and kept warm for 5h-7h; the substrate is heated to 295°C-305°C in the fourth stage and kept warm for 5h-7h; the substrate is heated to 545°C-555°C in the fifth stage and kept warm for 5h-7h.

[0014] Preferably, the microcapsules in step S2 are prepared by an in-situ polymerization method, wherein the wall material and the mixed stabilizer are dissolved in water, and then the core material is added, dispersed by high-speed stirring to form small droplets, and heated to polymerize the wall material on the surface of the core material to form microcapsules, wherein the wall material is sodium silicate, the core material is a dicyclopentadiene repair agent, and the emulsifier is sodium dodecylbenzene sulfonate; When microcracks appear in the coating due to environmental factors, physical damage or other reasons, the microcapsules rupture to release the internal repair agents, which then react chemically with the coating matrix to fill and repair the cracks, thereby restoring the integrity and functionality of the coating.

[0015] The present invention provides a method for using an anti-carburization coating, which has the following beneficial effects: The method for using the anti-carburizing coating is to add microcapsules to the anti-carburizing coating, which can give the coating multiple functions such as self-repair, anti-fouling, fire prevention, infrared cooling, etc. The microcapsules can encapsulate the repair agent. When the coating is damaged, the microcapsules rupture to release the repair agent, automatically repair the coating damage, and extend the service life of the coating. The density and anti-seepage performance of the coating can be improved by the nano-silicon dioxide in the coating. Nanomaterials can effectively improve the overall performance of the coating due to their small size effect and surface effect, solve the current situation of steel plate corrosion due to carburization, make the furnace insulation effect better, the anti-carburizing effect better, greatly shorten the process time, greatly reduce the use cost and maintenance cost, and extend the service life of the equipment. Compared with other anti-corrosion coatings, the anti-carburizing coating is not easy to age, fall off, or crack, and has a longer service life, thereby saving replacement and maintenance costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic diagram of the process of the present invention; Figure 2 It is a schematic diagram of the coating area of ​​the anti-carburizing coating of the present invention. DETAILED DESCRIPTION

[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0018] See also Figure 1-2 The embodiment of the present invention provides a technical solution: a method for using an anti-carburizing coating, the steps of which are as follows: S1: Pretreatment of substrate surface; clean the substrate surface thoroughly to remove oil and rust. First, wipe off the anti-rust oil with cotton yarn, then use 8112 cleaning agent to wash off the residual oil. After cleaning, put it into the furnace and keep it at 400℃ for 4 hours to remove the oil. For rust that is difficult to peel off, use mechanical removal methods such as sandblasting, shot blasting or chemical cleaning. The chemical cleaning method is to soak the substrate in 15% NaOH solution at 80℃ for 3 hours; S2: stirring of the coating; the prepared microcapsules are evenly dispersed in the coating matrix, and the microcapsules are prepared by in-situ polymerization, by dissolving the wall material and the mixed stabilizer in water, and then adding the core material, and then stirring and dispersing at high speed to form small droplets, and heating to polymerize the wall material on the surface of the core material to form microcapsules, wherein the wall material is sodium silicate, the core material is dicyclopentadiene repair agent, and the emulsifier is sodium dodecylbenzene sulfonate. The coating is fully stirred before application, and is stirred using a shaking bottle, a stainless steel rod or an electric stirrer. After stirring, the coating is poured into a stainless steel or plastic cup for use; when dipping, the working temperature is 30°C, the thickness of one dip is controlled at 30 microns, when spraying, the spraying distance is controlled at 35cm, and the moving speed of the spray gun is controlled within the range of 60 cm / second; when brushing, the part of the brush immersed in the coating should not exceed half of the length of the bristles, and the brush should be kept perpendicular to the coating surface when brushing, the force and speed are uniform, and the brushing is carried out alternately vertically and horizontally, and the brushing order is first up and then down, first left and then right, and first inside and then outside; S3: Coating; the coating is applied by brushing, spraying or dipping; the coating should be uniform, the thickness of the anti-carburizing coating is controlled at 0.2mm, and the coating density is 2.5g / cm³; S4: Drying of the coating; natural drying can be achieved by placing it in a ventilated place at room temperature for 24 hours, or baking it in a 60℃ oven for 2 hours; S5: Staged heating and insulation; after the coating is dried, the carburizing furnace is heated and insulated in stages. The multi-stage stepped heating is respectively the first stage, the second stage, the third stage, the fourth stage and the fifth stage. Among them, in the first stage, the substrate is heated to 45°C and kept warm for 26 hours. In the second stage, the substrate is heated to 85°C and kept warm for 7 hours. In the third stage, the substrate is heated to 105°C and kept warm for 7 hours. In the fourth stage, the substrate is heated to 305°C and kept warm for 7 hours. In the fifth stage, the substrate is heated to 555°C and kept warm for 7 hours.

[0019] The anti-carburizing performance of the carburizing furnace after staged heating and insulation requires that the maximum carbon increase within 1mm is less than 0.11%, the air gap should be controlled at ≤0.05mm, and the refractoriness should reach ≥1500℃.

[0020] In S1, the pores and honeycomb defects on the substrate surface need to be repaired and cleaned with a high-pressure water gun. The substrate surface is also pretreated, including pickling, acid solution immersion, and anodizing to form a layer of chemical substances on the substrate surface to improve the metal deposition effect. The preprocessing steps are: Step 1: Use a mixed pickling solution of hydrochloric acid, phosphoric acid, hydrogen peroxide and stabilizer for 2 minutes at room temperature; Step 2: Use a mixed pickling solution of hydrofluoric acid, sulfuric acid, hydrogen peroxide, etc., pickling time is 3 minutes, also at room temperature; Step 3: Soak the substrate in hydrochloric acid solutions of different concentrations (0.1, 1, 2 mol / L).

[0021] Step 4: Anodization: The substrate is placed as an anode in an electrolyte containing sulfuric acid, oxalic acid, chromic acid, etc., and electrolyzed under the action of an external current to form an oxide film with a thickness of 30 microns. The hard anodized film can reach 150 microns.

[0022] The coating in S2 is composed of the following components and mass fractions: 15 anti-carburizing agent, 125 glass powder, 10 silicon dioxide powder, 10 borax, 6 aluminum oxide, 8 dolomite powder, 50 sodium silicate, 10 nano silicon dioxide and the remainder water; the anti-carburizing agent is copper oxide powder with a purity of ≥99.0% and a particle size range of 200 mesh; the dolomite powder refers to dolomite powder containing 30.4% calcium oxide by mass and 21.9% magnesium oxide by mass.

[0023] The coating preparation method is as follows: Step 1: Grind the formulated anti-carburizing agent, glass powder, nano-silicon dioxide, silicon dioxide, borax, alumina and dolomite powder in a ball mill. The speed of the ball mill is 500 rpm. The discharge temperature after grinding is lower than 30°C. The grinding time is 90 minutes. The powder with a particle size of D≤10μm is set aside. Step 2: Add the formulated water glass to the powder in step 1, stir evenly, and when the viscosity reaches the range of 7000mPa•s, a finished anti-carburizing coating is obtained. The mass percentage of borax is ≥99.5%, and the particle size range is 80 mesh; the mass percentage of silicon dioxide is ≥99.0%, and the particle size range is 200 mesh; the mass percentage of alumina is ≥99.0%, and the particle size range is 230 mesh. Example 2

[0024] A method for using an anti-carburizing coating, comprising the following steps: S1: Pretreatment of substrate surface; clean the substrate surface thoroughly to remove oil and rust. First, wipe off the anti-rust oil with cotton yarn, then use 8112 cleaning agent to wash off the residual oil. After cleaning, put it into the furnace and keep it at 400℃ for 2 hours to remove the oil. For rust that is difficult to peel off, use mechanical removal methods such as sandblasting, shot blasting or chemical cleaning. The chemical cleaning method is to soak the substrate in 10% NaOH solution at 60℃ for 2 hours; S2: stirring of the coating; the prepared microcapsules are uniformly dispersed in the coating matrix. The microcapsules are prepared by in-situ polymerization, by dissolving the wall material and the mixed stabilizer in water, then adding the core material, and dispersing them through high-speed stirring to form small droplets, and heating to polymerize the wall material on the surface of the core material to form microcapsules, wherein the wall material is sodium silicate, the core material is dicyclopentadiene repair agent, and the emulsifier is sodium dodecylbenzene sulfonate. The coating is fully stirred before application, and is stirred using a shaking bottle, a stainless steel rod or an electric stirrer. After stirring, the coating is poured into a stainless steel or plastic cup for use; when dipping, the working temperature is 15°C, the thickness of one dip is controlled at 20 microns, when spraying, the spraying distance is controlled at 30 cm, and the moving speed of the spray gun is controlled within the range of 30 cm / second; when brushing, the part of the brush immersed in the coating should not exceed half of the length of the bristles, and the brush should be kept perpendicular to the coating surface when brushing, the force and speed are uniform, and the brushing is carried out alternately vertically and horizontally, and the brushing order is first up and then down, first left and then right, and first inside and then outside; S3: Coating; the coating is applied by brushing, spraying or dipping; the coating should be uniform, the thickness of the anti-carburizing coating is controlled at 0.1mm, and the coating density is 2.1g / cm³; S4: Drying of the coating; natural drying can be achieved by placing it in a ventilated place at room temperature for 24 hours, or baking it in a 60℃ oven for 2 hours; S5: stage heating and insulation; after the coating is dried, the carburizing furnace is heated and insulated in stages. The multi-stage stepped heating is respectively the first stage, the second stage, the third stage, the fourth stage and the fifth stage. Among them, in the first stage, the substrate is heated to 35°C and kept warm for 22 hours. In the second stage, the substrate is heated to 75°C and kept warm for 5 hours. In the third stage, the substrate is heated to 95°C and kept warm for 5 hours. In the fourth stage, the substrate is heated to 295°C and kept warm for 5 hours. In the fifth stage, the substrate is heated to 545°C and kept warm for 5 hours.

[0025] The anti-carburizing performance of the carburizing furnace after staged heating and insulation requires that the maximum carbon increase within 1mm is less than 0.11%, the air gap should be controlled at ≤0.05mm, and the refractoriness should reach ≥1500℃.

[0026] In S1, the pores and honeycomb defects on the substrate surface need to be repaired and cleaned with a high-pressure water gun. The substrate surface is also pretreated, including pickling, acid solution immersion, and anodizing to form a layer of chemical substances on the substrate surface to improve the metal deposition effect. The preprocessing steps are: Step 1: Use a mixed pickling solution of hydrochloric acid, phosphoric acid, hydrogen peroxide and stabilizer for 2 minutes at room temperature; Step 2: Use a mixed pickling solution of hydrofluoric acid, sulfuric acid, hydrogen peroxide, etc., pickling time is 3 minutes, also at room temperature; Step 3: Soak the substrate in hydrochloric acid solutions of different concentrations (0.1, 1, 2 mol / L).

[0027] Step 4: Anodization: The substrate is placed as an anode in an electrolyte containing sulfuric acid, oxalic acid, chromic acid, etc., and electrolyzed under the action of an external current to form an oxide film with a thickness of 5 microns. The hard anodized film can reach 25 microns.

[0028] The coating in S2 is composed of the following components and mass fractions: 10 anti-carburizing agent, 19 glass powder, 6 silicon dioxide powder, 5 borax, 3 aluminum oxide, 4 dolomite powder, 40 sodium silicate, 6 nano silicon dioxide and the remainder water; the anti-carburizing agent is copper oxide powder with a purity of ≥99.0% and a particle size range of 180 mesh; the dolomite powder refers to dolomite powder containing 28% calcium oxide by mass and 18% magnesium oxide by mass.

[0029] The coating preparation method is as follows: Step 1: Grind the formulated anti-carburizing agent, glass powder, nano-silicon dioxide, silicon dioxide, borax, alumina and dolomite powder in a ball mill. The speed of the ball mill is 400 rpm. The discharge temperature after grinding is lower than 30°C. The grinding time is 70 minutes. The powder with a particle size of D≤10μm is set aside. Step 2: Add the formulated water glass to the powder in step 1, stir evenly, and when the viscosity reaches the range of 6000mPa•s, a finished anti-carburizing coating is obtained. The mass percentage of borax is ≥99.5%, and the particle size range is 70 mesh; the mass percentage of silicon dioxide is ≥99.0%, and the particle size range is 170 mesh; the mass percentage of alumina is ≥99.0%, and the particle size range is 200 mesh.

[0030] By comparing the samples coated with anti-carburizing paint with those not coated with anti-carburizing paint, the coated areas such as Figure 2 As shown, the average carbon content (%) within 1 mm depth of the surface was measured, and the results were averaged, as shown in the following table: project Average carbon content within 1 mm depth of the surface (%) Embodiment 1: 0.07 Example 2 0.05 No anti-carburizing paint is used 0.33 In summary, the present invention solves the current situation of steel plate corrosion caused by carburizing, so that the furnace insulation effect is better, the anti-carburizing effect is better, the process time is greatly shortened, the use cost and maintenance cost are greatly reduced, and the service life of the equipment is extended.

[0031] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claims involved.

[0032] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for using an anti-carburizing coating, characterized in that: The steps are as follows: S1: Pretreatment of the substrate surface; clean the substrate surface thoroughly to remove oil and rust. First, wipe off the anti-rust oil with cotton yarn, then use 8112 cleaning agent to wash off the residual oil. After cleaning with the cleaning agent, put it into the furnace and keep it at 400℃ for 2-4 hours to remove the oil. S2: stirring the coating; the prepared microcapsules are evenly dispersed in the coating matrix, and the coating is fully stirred before application, using a shake bottle, a stainless steel rod or an electric stirrer for stirring. After stirring, the coating is poured into a stainless steel or plastic cup for use; S3: Coating; the coating is applied by brushing, spraying or dipping; the coating should be uniform, the thickness of the anti-carburizing coating should be controlled at 0.1-0.2mm, and the coating density should be 2.1-2.5g / cm³; S4: Drying of the coating; natural drying can be achieved by placing it in a ventilated place at room temperature for 24 hours, or baking it in a 60℃ oven for 2 hours; S5: Staged heating and heat preservation: After the coating is dried, the carburizing furnace is heated and heat preserved in stages.

2. The method for using an anti-carburizing coating according to claim 1, characterized in that: The anti-carburizing performance of the carburizing furnace after the staged heating and insulation requires that the maximum carbon increase within 1 mm is less than 0.11%, the air gap should be controlled at ≤0.05 mm, and the refractoriness should reach ≥1500°C.

3. The method for using an anti-carburizing coating according to claim 1, characterized in that: In S1, for the rust that is difficult to peel off, a mechanical removal method such as sandblasting, shot blasting or chemical cleaning is used. The chemical cleaning method is performed by soaking the substrate in a 10%-15% NaOH solution at 60-80° C. for 2-3 hours.

4. The method for using an anti-carburizing coating according to claim 1, characterized in that: In the S1, the pores and honeycomb defects on the surface of the substrate need to be repaired and cleaned with a high-pressure water gun, and the surface of the substrate needs to be pretreated, including pickling, acid solution immersion, and anodizing to form a layer of chemical substances on the surface of the substrate to improve the metal deposition effect.

5. The method for using an anti-carburizing coating according to claim 1, characterized in that: The coating in S2 is composed of the following components and mass fractions: 10-15 anti-carburizing agent, 19-25 glass powder, 6-10 silicon dioxide powder, 5-10 borax, 3-6 aluminum oxide, 4-8 dolomite powder, 40-50 sodium silicate, 6-10 nano silicon dioxide and the remainder water; wherein the anti-carburizing agent is copper oxide powder with a purity of ≥99.0% and a particle size range of 180-200 mesh; and the dolomite powder refers to dolomite powder containing 28%-30.4% calcium oxide by mass and 18%-21.9% magnesium oxide by mass.

6. The method for using the anti-carburizing coating according to claim 5, characterized in that: The coating preparation method is as follows: Step 1: Grind the anti-carburizing agent, glass powder, nano-silicon dioxide, silicon dioxide, borax, alumina and dolomite powder in a ball mill. The speed of the ball mill is 400rpm-500rpm. The discharge temperature after grinding is lower than 30°C. The grinding time is 70-90min. The powder with a particle size D≤10μm is set aside. Step 2: Add the formulated amount of water glass to the powder in step 1, stir evenly, and when the viscosity reaches the range of 6000mPa•s-7000mPa•s, the finished anti-carburizing coating is obtained.

7. The method for using the anti-carburizing coating according to claim 5, characterized in that: The mass percentage of the borax is ≥99.5%, and the particle size range is 70-80 mesh; the mass percentage of the silicon dioxide is ≥99.0%, and the particle size range is 170-200 mesh; the mass percentage of the aluminum oxide is ≥99.0%, and the particle size range is 200-230 mesh.

8. The method for using an anti-carburizing coating according to claim 1, characterized in that: In the S3, when dip coating is adopted, the working temperature is 15-30° C., the thickness of one dip coating is controlled at 20-30 μm, when spray coating is adopted, the spraying distance is controlled at 30-35 cm, and the moving speed of the spray gun is controlled at the range of 30-60 cm / s.

9. The method for using an anti-carburizing coating according to claim 1, characterized in that: The multi-stage stepped heating is respectively the first stage, the second stage, the third stage, the fourth stage and the fifth stage, wherein the first stage heats the substrate to 35°C-45°C and keeps it warm for 22h-26h, the second stage heats the substrate to 75°C-85°C and keeps it warm for 5h-7h; the third stage heats the substrate to 95°C-105°C and keeps it warm for 5h-7h; the fourth stage heats the substrate to 295°C-305°C and keeps it warm for 5h-7h; the fifth stage heats the substrate to 545°C-555°C and keeps it warm for 5h-7h.

10. The method for using the anti-carburizing coating according to claim 1, characterized in that: The microcapsules in step S2 are prepared by an in-situ polymerization method, which comprises dissolving the wall material and the mixed stabilizer in water, then adding the core material, and dispersing them through high-speed stirring to form small droplets, and heating to polymerize the wall material on the surface of the core material to form microcapsules, wherein the wall material is sodium silicate, the core material is a dicyclopentadiene repair agent, and the emulsifier is sodium dodecylbenzene sulfonate.

Citation Information

Patent Citations

  • Inorganic anti-carburizing coating and preparation method thereof

    CN110105796A

  • Construction method of high-impermeability concrete

    CN112982417A

  • Use method of anti-nitriding coating

    CN115323310A